Surface analysis of polymers by XPS and static SIMS - Briggs, D (Cambridge University Press, 1998)
This in-depth treatment of the instrumentation, physical bases and applications of x-ray photoelectron spectroscopy (XPS) and static secondary ion mass spectroscopy (SSIMS) contains a specific focus on the subject of polymeric materials. XPS and SSIMS are widely accepted as the two most powerful techniques for polymer surface chemical analysis, particularly in the context of industrial research and problem solving.